Labor Market Performance in OECD Countries: The Role of Institutional Interdependencies - Andreas Sachs; Frauke Schleer (International Economic Journal, 2019)
Reducing rigidity in labor markets is key to lowering unemployment. Theoretical models suggest that the impact of such reforms depends on the country-specific regulatory framework. We test this hypothesis by estimating the impact of changes in six categories of regulation conditional on the country-specific regulatory environment for 26 OECD countries. We overcome problems of modeling a large set of institutional interdependencies by applying a machine learning type model selection approach. We provide evidence for the existence of higher-order institutional interdependencies. We further document that especially for changes in employment protection and the unemployment benefit system the impact on unemployment is mixed across countries.
Keywords: C33; E02; E24; 330; Labor market regulation; unemployment; institutional interdependencies; model selection; heuristic optimization; machine learning